2021
DOI: 10.1002/er.7149
|View full text |Cite
|
Sign up to set email alerts
|

Large scale synthesis of hexagonal boron nitride nanosheets and their use in thermally conductive polyethylene nanocomposites

Abstract: Despite their isostructural similarity to graphene, large-scale preparation of hexagonal boron nitride nanosheets (hBNNs) has been challenging, mainly due to their strong interlayer interactions initiated by the electronegativity difference in their elemental components. In this study, a large-scale synthesis of hBNNs via a ball milling (BM) technique is reported. The hBN exfoliation was optimized by analyzing the effect of the ball milling process parameters (ball to powder ratio, speed, and time) on the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Ali et al explored the influence of milling parameters on the quality and yield of BNNS. 54 It was found that the optimum milling conditions are a ratio of 10:1 ball to powder and rotation speed of 250 rpm. Besides, the introduction of ball milling additives is also conductive to achieving their synergistic surface functionalization.…”
Section: Mechanical Exfoliationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al explored the influence of milling parameters on the quality and yield of BNNS. 54 It was found that the optimum milling conditions are a ratio of 10:1 ball to powder and rotation speed of 250 rpm. Besides, the introduction of ball milling additives is also conductive to achieving their synergistic surface functionalization.…”
Section: Mechanical Exfoliationmentioning
confidence: 99%
“…Moreover, the lateral diameter and yield of BNNS are closely related to the ball milling parameters, including the ball size, extra additives, speed, and time. Ali et al explored the influence of milling parameters on the quality and yield of BNNS 54 . It was found that the optimum milling conditions are a ratio of 10:1 ball to powder and rotation speed of 250 rpm.…”
Section: Preparation Of Bnnsmentioning
confidence: 99%
“…Besides the improved optical properties and chemical stability; with their high surface area, they reduce interchain mobility and improve the mechanical and thermal properties of polymers. Due to their fascinating properties, they have great potential in various applications including coatings, automotive, catalysts, medicine, sensors, electronics, high-resolution imaging, energy storage, water purification, and UV emitters [16][17][18][19]. The h-BNNs can be prepared by using various methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting as well as challenging to study the elastic properties of BNNS due to the involvement of their atomistic structural parameters. Recent studies by Ali and Abdala [27] worked on the synthesis of h-BN by ball milling and analysed the effect of the same concerning speed and time, which resulted in enhancing the thermo-mechanical properties of nanocomposites. Choyal et al [28] investigated the effect of E on boron nitride nanotubes using MD simulation and found that the value of E increases as the AR increases.…”
Section: Introductionmentioning
confidence: 99%